Körper :-) Wahrnehmung. Eine Seminarübung mit Dietriu Zilleßen - Schroeter-Wittke, Harald; Fermor, Gotthard; Zilleßen, Dietrich (Prozesse postmoderner Wahrnehmung. Kunst - Religion - Pädagogik)

Homiletische Überlegungen zu I Kön 18 - Schroeter-Wittke, Harald; Schroeter, Britta (Elia. Ein Prophet in dürrer Zeit - Materialien zur Gottesdienstgestaltung. Thema: Gottesdienst)

Der Dienst der öffentlichen Verkündigung in einer missionarischen Situation - Schroeter-Wittke, Harald (Der Dienst der öffentlichen Verkündigung in einer missionarischen Situation)

Kirchentag als Gesamtkunstwerk. Ein Bericht über seine kulturellen Dimensionen - Schroeter-Wittke, Harald (Kirche und Kultur der Gegenwart)

"Schweigendes Buch" - Zu einer Kunstaktion des Siegburger Künstlers Robby Gebhardt - Schroeter-Wittke, Harald (Thema: Gottesdienst)

"Schweigendes Buch" - Zu einer Kunstaktion von Robby Gebhardt - Schroeter-Wittke, Harald (Der Evangelische Erzieher)

On the Observability of dynamic localization in semiconductor superlattices using optical spectroscopy - Meier, Torsten; Rossi, F.; Je, K.-C; Hader, J.; Thomas, P.; Koch, S.W. (Hot Carriers in Semiconductors)
During the last decade, a variety of field-induced coherent phenomena in semiconductor superlattices has received considerable attention both from a theoretical and from an experimental point of view. For the case of a static applied electric field, the existence of Bloch oscillations has been predicted theoretically and confirmed by means of different experimental techniques of nonlinear optical spectroscopy.

Microscopic theory of the Bloch-oscillation dynamics in semiconductor superlattices: Intra- versus interband Dephasing - Meier, Torsten; Rossi, F.; Gulia, M.; Selbmann, P.E.; Molinari, E.; Thomas, P.; Thomas, P.; Koch, S.W. (Proceedings of the 23rd ICPS)

Exciton ionization induced by an electric field in a strongly coupled GaAs/AlxGa1-xAs superlattice - Meier, Torsten; von Plessen, G.; Koch, M.; Feldmann, J.; Thomas, P.; Koch, S.W.; Göbel, E.O.; Goosen, K.W.; Kuo, J.M.; Kopf, R.F. (Physical Review-Section B-Condensed Matter)
We study exciton ionization induced by an axial electric field in a strongly coupled GaAs/Al0.3Ga0.7 As superlattice at low temperatures. The field-induced ionization times of the heavy-hole 1s exciton in the miniband field regime are determined from transient four-wave-mixing experiments and theoretical model calculations. They are found to decrease with increasing field, and lie in the picosecond and subpicosecond ranges for fields on the order of a few kV/cm. They are considerably longer than those calculated for a 1s exciton in bulk GaAs. We explain this difference as a result of the nonparabolicities in the superlattice miniband dispersion. In addition to studying the field-induced ionization of the 1s resonance, we also investigate the field dependence of excitonic wave packets composed of both bound and continuum states of the exciton. It is found that the continuum components of the wave packet are more sensitive to low electric fields than the 1s component. © 1996 The American Physical Society.

Disorder mediated biexcitonic beats in semiconductor quantum wells - Meier, Torsten; Albrecht, T.F.; Bott, K.; Schulze, A.; Koch, M.; Cundiff, S.T.; Feldmann, J.; Stolz, W.; Thomas, P.; Koch, S.W.; Göbel, E.O. (Physical Review B)
Beats in the transient four-wave-mixing signal from strongly inhomogeneously broadened semiconductor quantum wells are observed. Based on their phase and polarization properties, the beats are assigned to biexcitons in the mesoscopically disordered material. With increasing excitation intensity a halving of the beat period is observed and is accurately reproduced by calculations including fifth-order contributions.